Central Partial Mastectomy in Patients with Centrally Located Breast Tumors - Abdelkadir Hegazy, Ahmed; Farahat, Ahmed Mohamed; Mahmoud Amin, Amr; Mustafa Manie, Tamer; Zakaria Yousef, Omar (Journal of Neonatal Surgery, 2025)
Background: Oncoplastic surgery (OPS) is crucial for centrally located breast cancers (CLBCs) to enable safe tumor resection, while maintaining good cosmetic outcomes. This study illustrated the results of women with CLBC having various surgical methods for partial breast reconstruction after central quadrantectomy. Methods: This prospective cohort study involved 30 patients with CLBC scheduled for OPS. The surgical techniques were decided by a multi-disciplinary team considering tumor size and location, breast size, degree of ptosis, ratio of breast to tumor size, nodal status, and nipple involvement. The postoperative cosmetic appearance was assessed after four weeks as a patient-reported outcomes (PROs) using a five-point scale. Results: The average age of the cohort was 46.8±9.1 years. The tumor was retroareloar in 11 patients and periareolar in 19. Nodal involvement was identified in 12 cases (40%). Nipple-areola complex was involved in 9 patients (30%). Techniques performed were crescentic excision (n=9), round block (n=8), and reduction mammoplasty (n=2) in the periareolar group. In the retroareolar group, Grisotti flap (n=4), reduction mammoplasty (n=2), crescentic excision (n=2), central quadrantectomy followed by 1ry (n=2) or purse string closure (n=1) were performed. Excellent and good cosmetic outcomes were reported by 83.3% of the patients. Operative complications were trivial and observed in a few patients including seroma, wound infection, and loss of nipple sensitivity. Conclusion: Oncoplastic surgery in patients with CLBC depending on the tumor location, breast size and degree of ptosis achieved excellent and good results with the application of different surgical techniques.